A Case Study Community Empowerment through the Food Security Program: A Case Study of Nagari Anam Koto Selatan, Kecamatan Kinali, Kabupaten Pasaman Barat - Handraini, Helti; Alhadi, Zikri (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
This study aims to analyze community empowerment through the Food Security Program in Nagari Anam Koto Selatan, Kinali District, West Pasaman Regency. It addresses challenges arising from the community’s low post-training independence, suboptimal program sustainability, and insufficient attention to nutritional and food‐safety aspects. A descriptive qualitative method was employed, with data collection comprising in‐depth interviews, participatory observation, and documentation, supported by source and method triangulation to ensure data validity. Findings indicate that the principles of equity and participation have been well implemented through training and mentoring; however, community independence remains low, and post‐training sustainability is not yet optimal. Although food production has shown intermittent increases and food access has improved via cooperatives, attention to nutrition and food safety remains inadequate. The principal impediments include limited human resources, inadequate infrastructure, insufficient capital, and weak inter‐agency coordination. The study underscores the need to strengthen HR capacity through locally tailored training, provide intensive post‐training mentoring, optimize the allocation of Village Funds for production facilities and infrastructure, and reinforce local institutions such as the LPMN, PKK, and Karang Taruna. These insights are intended to guide the Nagari government and relevant stakeholders in formulating more effective and sustainable community-empowerment strategies.